Glucose levels in first 3 days and neurodevelopmental outcome at 1 year in low birth weight infants: A cohort study - Chandrasekaran, Ashok; Rao, P N Suman; Raman, Vijaya; Nesargi, Saudamini; Shekharappa, Chandrakala Bada; Sahoo, Jagdish Prasad; Ranjit, Thomas; Chico, Marie Shalini; Bhat, Swarnarekha (Indian Journal of Child Health, 2016)
Background: Definition of neonatal hypoglycemia is still controversial. Objective: To find the effect of blood glucose (BG) levels in the first 3 days of life, on developmental outcome at 1 year in low birth weight neonates <2000 g. Methods: A prospective cohort study was conducted in tertiary level neonatal intensive care unit and follow-up clinic in south India. Intramural neonates admitted from September 2009 to August 2010 were enrolled. Perinatal and neonatal variables were recorded. Respiratory support, fluids, and feeding management were based on the standard protocols. BG was measured within 2 h, then 6 hourly for 72 h by glucometer and BG <50 mg% was analyzed by hexokinase method. Infants were followed until 1 year corrected age and development age (DA) assessed by Developmental Assessment Scales for Indian Infants (DASII). Motor and mental DA at various BG levels were compared. Composite outcome of motor or mental developmental delay; or cerebral palsy or hearing impairment or visual impairment was analyzed, and logistic regression analysis was performed. Results: The mean birth weight and gestation of the study group (n=129) was 1493 g and 32.5 weeks. The 10th centile of BG in the first 72 h was 51 mg%. BG below 10th centile was seen in 60 infants. The mean motor and mental DA of the infants by DASII assessment at 1 year was 11.3 and 11.5 months, respectively. The motor DA and mental DA were significantly higher until 50 mg% lowest BG level, and positive correlation was seen (r=0.26 motor, 0.2 mental DA). Mean BG level, the presence of symptoms; number of episodes or small for gestation did not influence the DA. The adjusted odds for poor composite outcome when BG was below 51 mg% is 2.83 (0.65-12.3). Conclusion: Even though high-risk neonates with BG <51 mg% have a lower motor DA and mental DA at 1 year, than neonates with BG >50 mg%; other morbidities do determine their composite outcome.